Evaluation of the Effect of Nasal Septal Deviation and Concha Bullosa on Maxillary Sinus Volume by Cone Beam Computed Tomography - Emin Murat Canger; Beyza Yalvaç; Meryem Kaygısız Yiğit; Rıdvan Akyol; Fatma Dilek (Ankara University, 2023)
Purpose: The aim of this study was to examine, using cone beam computed tomography images, the direction and severity of nasal septal deviation as well as the relationship between the presence of concha bullosa with maxillary sinus volume. Materials Methods: In this retrospective study, images of 50 individuals who had been referred for cone beam computed tomography imaging for a variety of reasons were used. Age, gender, the direction and severity of the nasal septal deviation, and the presence and types of concha bullosa, were all investigated. The maxillary sinus volume was calculated using the Simplant Pro 16 program (Materialise NV, Leuven, Belgium). SPSS v.22 software was used for all statistical analyses. The statistical significance level was accepted as p